Detection of foot-and-mouth disease virus RNA using a closed loop-mediated isothermal amplification system - Edwards, Natasha; Reboud, Julien; Yan, Xiaoxiang; Guo, Xin; Cooper, Jonathan M.; Wadsworth, Jemma; Waters, Ryan; Mioulet, Valerie; King, Donald P.; Shaw, Andrew E. (Frontiers in Microbiology, 2024)
Foot-and-mouth disease (FMD) is a highly contagious viral disease of cloven-hoofed animals responsible for economic losses that amount to >20 billion annually. Rapid recognition of FMD cases provides vital information to guide control programs. A range of point-of-need (PON) amplification technologies have been developed which allow sensitive detection of the causative virus (FMDV) in the field at locations remote from laboratories. Here we describe a novel system to detect FMDV RNA using loop mediated isothermal amplification (LAMP). This test was evaluated using a panel of FMDV isolates (n=79) and RNA standards demonstrating capability to amplify viral genome directly from clinical material in the absence of nucleic acid extraction. This extraction-free RT-LAMP assay was transferred to a bespoke closed-system lateral flow test (LFT) that was used in combination with a lowcost hand-held heater. Our results show that the RT-LAMP-LFT assay retains a high level of diagnostic and analytical sensitivity when using direct clinical material, with a limit of detection of approximately 80 copies per reaction. Together, our data support the potential for the use of this assay at the PON to facilitate rapid feedback on the status of suspect cases.